The Practices of Cognitive Reading Strategies on Freshman Students’ Reading Comprehension: The Case of Addis Ababa University - Seyoum, Worku; Barkasa, Mendida (Inspiring: English Education Journal, 2026)
English plays an important role in Ethiopian education and daily communication. This makes teaching effective reading strategies necessary for comprehension. Despite this significance, little local research has looked into how reading strategies connect to the reading skills of first-year students at Addis Ababa University. Therefore, this study examined how often Addis Ababa University’ freshmen use reading strategies and how English instructors incorporate these techniques in their classrooms. Using a mixed-methods design, data were collected from two groups of 96 students through surveys and classroom observations. Addis Ababa University was selected through convenience sampling due to its accessibility and similarities—like class size, resources, and teaching environment—to other public universities. Researchers analyzed the quantitative data first, followed by qualitative analysis for triangulation. The results showed that students used reading strategies at a moderate level, primarily relying on problem-solving strategies (M = 3.70), then support strategies (M = 3.37), and finally global strategies (M = 3.36). However, teachers tended to focus little on reading-strategy instruction. The findings suggest that instructors should better promote various reading techniques to improve comprehension. Future studies should explore the long-term effects of clear cognitive strategy instruction in larger classroom contexts with bigger samples.